Dyslipidemia frequency in patients with plaque psoriasis: A cross-sectional study - Khan, Farooq Azam; Abdullah, Muhammad; Soomro, Amjad Hussain; Zubair, Muhammad; Ahmad, Jamil; Khan, Abdul Qayum (Journal of Neonatal Surgery, 2025)
Background: Psoriasis is a disorder of the skin that is non-contagious and has a long duration. It affects 1- 3% of the population. Psoriasis is a chronic disorder of the skin and associated with dyslipidemia. Objective: The aim of this study was to find out the frequency of dyslipidemia in individuals with plaque psoriasis Materials and method: The present cross-sectional study was conducted at the dermatology department Naseer ullah Khan Babar memorial hospital, Peshawar from January 2025 to June 2025 after taking approval from the research committee of the hospital. Non probability sampling method was used and sample size was determined through WHO calculator. The size of the sample was 106 using 95% confidence level and 7% margin of error. Individuals of both genders and different age groups (ranged 15-65) years with chronic plaque psoriasis were included. SPSS Version 24 was used for data analysis. Results: A total of 106 individuals were enrolled in this study out of which 63 were males and 43 were females. The mean age of the study population was 38.77 with standard deviation 12.11(ranged 18-65) years. The participants were classified in to two age groups < 15-40 years and above 40 to 65 years. Based on the duration of the illness, individuals were divided into two groups. Those who have had the illness for less than ten years, whereas the other group has had it for more than ten years. The mean duration was 8.52±6.2 standard deviations, with a minimum of one year and a maximum of twenty-five years. Dyslipidemia was found in 36 (34%) of the selected individuals in the whole sample. It was found that 24% of patients had increased total cholesterol, 10% had higher triglycerides, 4% had greater low density lipoproteins, and 21% had elevated high density lipoproteins. There were 16 individuals with dyslipidemia in the 15–40 age group and 20 individuals in the 40–65 age group, with a substantial P-Value of less than 0.001. Dyslipidemia was discovered in 16 patients in the disease duration group under 10 years and in 20 patients in the duration group over 10 years, with a significant P Value less than 0.001. Conclusion: The present study concluded that dyslipidemia was most prevalent (34%) in individuals with plaque psoriasis and its frequency increased with the duration of the disease